Mexiletine in human blood and breast milk. Issue 671 (September 1981) - Lewis, A. M.; Patel, L.; Johnston, A.; Turner, P.
Abstract : Twelve paired samples of breast milk and blood were obtained, between the 2nd and 5th days after she had given birth, from a 30-year-old woman who was a 8-hourly propranolol (20 mg) and mexiletine (200 mg). Propranolol was detected in 9 of the samples of blood and in only 4 of the milk samples. Mexiletine was measurable in all samples, and the milk : plasma ratio varied between 0.79 and 1.89 with a mean of 1.45. However, the large volume of distribution of mexiletine makes it unlikely that the small dose of the drug received from the milk would be detrimental to the health of infants.